Code Mix Analysis on Buying and Selling Interactions at Bintang Kejora Jaya Restaurant - Ayu Puspita Indah Sari; Lela Sartika (RETORIKA: Jurnal Ilmu Bahasa, 2023)
This study aims to describe the form of code-mixing in the interaction of buying and selling at the Bintang Kejora Jaya Restaurant, as well as the factors causing the mixing of code codes in the exchange of buying and selling at the Bintang Kejora Jaya Restaurant. This type of research is qualitative research through a case study approach. Data collection techniques use listening, tapping, note-taking, and recording techniques. Data analysis techniques use descriptive methods. From the results of these findings, it was identified that there were findings of code mixing in the form of words, phrases, clauses, and word loops. Factors causing code-mixing include linguistic elements such as low word frequency, Pernicious humanity, Oversight, and End (purpose and goal).